Student’s Responses on the Suitability of Text Complexity Level Determination Using Web-Based Readability Analysis Application: A Systemic Functional Perspective - Ramadhani, Reski (Master Program in Linguistics, Diponegoro University, 2024)
The present study attempts to investigate the students' responses on the suitability of web-based readability analysis application results using the Systemic Functional Linguistics Framework through lexical density analysis with their level of language proficiency. This study used a qualitative method supported by some descriptive quantifications to analyze the lexical-density indexes of reading texts. Six texts were randomly selected from the reading texts written in five of Cambridge's Books, and nine participants at different levels were purposively selected to verify the accuracy. The findings revealed that the percentages of lexical density indexes of six selected Cambridge Books texts categorized based on the CEFR level used in this study and automatically analyzed by the application follow the complexity standard decided by the book's writers. Furthermore, the students at each level have a positive response to the text tested, as seen in their ability to answer the questions in each text created by the book's writers. This study provides the implication of informing educators to utilize the web-based readability analysis used in this study to help them analyze the text automatically, accurately, and quickly.